Efeitos psicofarmacológicos do óleo de krill em camundongos - Gouveia, Roberta de Araújo (2016)
Epilepsy is a neurological disease characterized by long duration disorders, where the most severe episode of this disorder is associated with seizure attacks. Science has been seeking new drugs, as well as unconventional treatments to provide quality of life for individuals affected by this disease. There is scientific evidence of an association between the fatty acid content of the diet and specific changes in neurotransmission system, especially polyunsaturated fatty acids, which are able to alter neuronal excitability, act as neuroprotective, in addition to possess anticonvulsant. This study aimed to investigate the possible anticonvulsant effects of krill oil (rich in polyunsaturated fatty acids) in the central nervous system of mice, evaluating even if it interferes with locomotor and / or muscle relaxation activity, and it has effects sedatives common to anticonvulsant drugs. We used 100 male Swiss mice were divided into control group (CG) received distilled water and krill Group (GK), which received the krill oil, both by gavage and the amount administered 1ml/100g of animal weight / day, for 30 days. Behavioral changes were analyzed on the 31st day through convulsive experiments (pilocarpine, electroshock and pentylenetetrazol), anxiolytics experiments (activity monitor, open, rota-rod and the elevated plus-maze). In the electroshock test the group submitted to supplementation with krill oil presented a shorter seizure when compared to the control group. In pentylenetetrazol test (PTZ) GK obtained a higher latency to onset of first seizure in addition to the reduction in tonic seizures and tonic-clonic, when compared to the CG. In the apparatus of the open field, it was observed an increase in immobility time, reduction in input frequency in the central quarters of the krill group, plus a reduction in peripheral ambulation compared to the control group. In Activity Monitor test, animals in the supplemented group traveled a shorter distance, less uptime and lower speed when compared to the control group. The results of the entry number in both the open arms and in the closed arms of the maze as well as the time spent in the open arms was not statistically significant, it was applied to pilocarpine and the test route rod. On krill oil the above is a possible candidate for the adjunctive treatment of seizures.